2016
DOI: 10.1177/0956797615620378
|View full text |Cite
|
Sign up to set email alerts
|

Money Cues Increase Agency and Decrease Prosociality Among Children

Abstract: People can get most of their needs broadly satisfied in two ways: by close communal ties and by dealings with people in the marketplace. These modes of relating-termed communal and market-often necessitate qualitatively different motives, behaviors, and mind-sets. We reasoned that activating market mode would produce behaviors consistent with it and impair behaviors consistent with communal mode. In a series of experiments, money-the market-mode cue-was presented to Polish children ages 3 to 6. We measured com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
80
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 31 publications
4
80
3
2
Order By: Relevance
“…The current study used money as the medium of exchange. Previous literature suggests that the inclusion of money may prompt children to adopt a more market-oriented perspective (Gasiorowska, Chaplin, Zaleskiewicz, Wygrab, & Vohs, 2016;Gasiorowska, Zaleskiewicz, & Wygrab, 2012). Contrary to this prediction, we did not find that distribution decisions differed when comparing no money and equal money trials.…”
Section: Discussioncontrasting
confidence: 99%
“…The current study used money as the medium of exchange. Previous literature suggests that the inclusion of money may prompt children to adopt a more market-oriented perspective (Gasiorowska, Chaplin, Zaleskiewicz, Wygrab, & Vohs, 2016;Gasiorowska, Zaleskiewicz, & Wygrab, 2012). Contrary to this prediction, we did not find that distribution decisions differed when comparing no money and equal money trials.…”
Section: Discussioncontrasting
confidence: 99%
“…Whereas adults are willing to incur personal costs to ensure equality between themselves and an anonymous stranger (e.g., an adult would rather share two dollars equally with a stranger, such that each receives one dollar, than receive two dollars and leave nothing for a stranger), this willingness does not seem to emerge until 7-8 years of age (e.g., Fehr, Bernhard, & Rockenbach, 2008;Sheskin, Bloom, & Wynn, 2014). These findings, in combination with recent work showing that young children behave more selfishly when handling monetary compared to non-monetary goods (Gasiorowska, Chaplin, Zaleskiewicz, Wygrab, & Vohs, 2016), suggest that attention to moral history may develop in tandem with children's increase in moral concern. Understanding this issue becomes important given our finding that moral history guides people's behavior and understanding of the material world.…”
Section: Discussionmentioning
confidence: 65%
“…Nonetheless, it is possible that the love of money primed concepts other than those discussed in this paper. For example, there is evidence showing that reminders of money make people work harder on competency tasks (e.g., Gasiorowska et al ., ; Vohs et al ., , ). Such performance motivation could have made participants in Study 2 focus more on the partner's competence which inevitably serves as a confound of usefulness.…”
Section: Discussionmentioning
confidence: 97%
“…While the current findings are in line with predictions by market‐pricing mode, they may not be explained purely from a functionalist perspective (i.e., maximization of gain and minimization of cost). Communal mode mentality, in which kindness and altruism are seen as central to social relations, lies at the opposite end of market pricing mode (Fiske, ; Gasiorowska, Chaplin, Zaleskiewicz, Wygrab, & Vohs, ). It has been demonstrated that money brings about behaviour that is consistent with market‐pricing mode (i.e., self‐gain and goal achievement) while it impairs behaviour consistent with the communal mode (i.e., pro‐sociality and generosity; Gasiorowska et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation